Monitoring Agricultural Land Loss by Analyzing Changes in Land Use and Land Cover - Morakot Worachairungreung; Nayot Kulpanich; Kunyaphat Thanakunwutthirot; Phonpat Hemwan (Emerging Science Journal, 2024)
The agricultural sector's output holds paramount significance for the global population, serving as an indispensable resource for survival and consumption. Consequently, alterations in agricultural landscapes bear substantial implications for the world's food supply. The objectives of this research are to investigate the depletion of agricultural land, with a specific focus on Samut Songkhram Province—an agriculturally prominent region in Thailand renowned for supplying seafood and fruits to Bangkok. By employing advanced remote sensing and change detection methods and incorporating indices like NDVI, NDWI, and NDBI, the study meticulously analyzed land-use changes. The outcomes were rigorously scrutinized through supervised classification, validated by on-site inspections, and corroborated with data from pertinent agencies. Findings revealed that Samut Songkhram had sustained its prominence in agricultural land, constituting around 70% of the province's total area over the past two decades. However, this expanse has undergone persistent transformation during the last 20 years. Notably, the most substantial surge was observed in the conversion of agricultural land to urban and developed areas, particularly in the urban zones of Amphawa District, followed by Mueang Samut Songkhram and Bang Khonthi districts. This investigation illuminates a consistent downward trend in agricultural land, a vital source of sustenance for Thailand's population and the global community. Doi: 10.28991/ESJ-2024-08-02-020 Full Text: PDF